Rehabilitation in palliative care: a qualitative study of team professionals. Issue Volume 12(2022)Issue e1 (30th December 2019) - Harding, Zoe; Hall, Charlie; Lloyd, Anna
Abstract : Objectives: There has been a recent drive to embed rehabilitation within palliative care. The concept of rehabilitative palliative care has been advocated to help patients preserve function and independence, through greater patient enablement and self-management. Such an approach requires engagement from all members of the palliative care team. There is a lack of understanding of such viewpoints. The objective of this research was to explore hospice-based palliative care professionals' understanding and perceptions of rehabilitation. Methods: Qualitative semi-structured interviews were conducted. Eighteen hospice-based healthcare professionals were recruited from a hospice in central Scotland. Interviews were audio-recorded, transcribed and thematically analysed. Results: Overall, participants clearly articulated the underlying values and benefits of rehabilitative palliative care. Emphasis was placed on ensuring that rehabilitation was appropriately tailored to each individual patient. There was more ambiguity regarding the pragmatic implementation of rehabilitative palliative care, with a number of barriers and facilitators identified. Conclusions: The findings suggest that hospice-based palliative care professionals would be receptive to further implementation of rehabilitative palliative care. A lack of conceptual clarity among palliative care professionals may be a barrier to the effective implementation of rehabilitative palliative care. At an organisational level, this would require clarification of the approach, and additional training involving all members of the multidisciplinary team.